Development of a layer-wise in-situ laser-based dimensional monitoring system with post-mechanical characterization of synthesized polylactic acid 3D prints in FDM additive manufacturing - Vishal V. Shukla; Yogesh G. Joshi; Niraj Kumar Dewangan (PLoS ONE, 2026)
High-dimensional accuracy is difficult to obtain in 3D printing techniques such as Fused Deposition Modeling (FDM). The study was conducted in two phases. In the first phase, the causes of dimensional inaccuracy in FDM printing were reviewed and a new Laser-Based Dimensional Measurement System (LDMS) was produced. Two FDM printers, Ultimaker Extended and Creality Ender 3 Pro, were used in experiments to investigate the impacts of material deposition, over-extrusion, print speed, under-extrusion, mechanical vibrations, and temperature variation on dimensional accuracy. The third stage involved the synthesis of PLA material, which was then extruded into a capillary and used for 3D printing by the LDMS system. The printed samples were characterized using tensile, hardness, and flexural tests, as well as XRD, FTIR, SEM, and TG/DA analyses. It was also demonstrated that the LDMS provides in-situ layer-wise dimensional monitoring during intermediate stages of the building process. The obtained PLA polymers were biodegradable and amorphous. It was also noted that the printed parts could withstand lateral loads better than longitudinal loads, and, in compression, they were stronger than in tension.This research work supports SDG 12 (Responsible Consumption and Production) by improving material efficiency and promoting biodegradable PLA.